Proposal of a Combined Environmental Management Solution for Municipal Solid Waste (MSW) Separation in a Developing Country: for Pilot Realization in Hanoi, Vietnam - Vuong Thi, Anh Lan; Hung, Do Manh (International Journal of Integrated Engineering, 2020)
Municipal solid waste (MSW), thousands of tons of which increasingly generated daily in human life by the rapid urbanization, population migration and industrialization not only in Vietnam, but in all developing countries are causing many serious problems in Environmental management for the authorities of these issues. In Vietnam, various approaches, solutions and programs were studied, suggested and deployed over the last decades, but the most of them have stopped at the level of pilot-programs and have generally not been replicable, so not been applied in wide scale. The most challenging issue of MSW management systems is non-applied or not fully - done waste separation practice at sources, caused by not only limited collection equipment, staff and working efficiency, but also lack of investment in infrastructure and limited public awareness. These circumstances raised the real need of a combined Environmental Management solution for municipal solid waste (MSW) separation at sources, especially in urban residential households. This paper proposes a combined management solution for municipal solid waste (MSW) separation at sources, based on applying and combining 4 main environmental management instruments: 1- Legislation, 2- Economic, 3- Analysis, assessment and technology, 4- Education and Communication. A pilot realization in Hanoi, Vietnam is proposed with detail description of the solution and reasonable argumentation. The solution effectiveness, judged on the basis of the collected data is presented.